Evaluasi kualitas situs web Perpustakaan Universitas Sebelas Maret berdasarkan persepsi mahasiswa - Nugraha, Airlangga Eka; Katrin Setio Devi (Universitas Islam Negeri Salatiga, 2025)
This study aims to evaluate the quality of services provided by the Universitas Sebelas Maret Library Situs web based on user perceptions. The assessment focuses on five key dimensions of the Delone and McLean information system success model: system quality, information quality, service quality, use, and user satisfaction. A descriptive quantitative approach was employed in this study, with data collected through an online questionnaire distributed to 30 active UNS students who had experience using the library website. The findings reveal that all dimensions received high scores, with user satisfaction being the highest (effectiveness 93.4%, efficiency 90%). System quality, information quality, and use also received positive evaluations. However, the service quality dimension, particularly in terms of speed and responsiveness, still requires improvement. These results highlight the importance of enhancing digital service responsiveness and integrating library services into the broader online learning ecosystem. This study contributes to the development of user perception–based evaluation systems for digital information services in higher education, and offers strategic recommendations for improving the quality and sustainability of digital library service usage.